2017
DOI: 10.1080/08923973.2017.1405439
|View full text |Cite
|
Sign up to set email alerts
|

Hecogenin exhibits anti-arthritic activity in rats through suppression of pro-inflammatory cytokines in Complete Freund’s adjuvant-induced arthritis

Abstract: Hecogenin is a steroidal sapogenin isolated from the leaves of Agave genus species that plays an important role in the treatment of a variety of inflammatory diseases. The aim of the present study was to evaluate the anti-arthritic activity of hecogenin in Complete Freund's adjuvant-induced arthritis in rats. The hecogenin (40 µl of 50 µg/kg, orally) and hecogenin + fluticasone (40 µl of 25 µg/kg, each, orally) was tested against Complete Freund's adjuvant-induced arthritis in rats by evaluating various parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Macrophages activation in turn activate the proinflammatory cytokines such as TNF-a and IL-6 [41]. Arthritic index score is also increased to significant extent in CFA induced rats [42] and nimbolide treatment reduced the arthritic index score.…”
Section: Discussionmentioning
confidence: 96%
“…Macrophages activation in turn activate the proinflammatory cytokines such as TNF-a and IL-6 [41]. Arthritic index score is also increased to significant extent in CFA induced rats [42] and nimbolide treatment reduced the arthritic index score.…”
Section: Discussionmentioning
confidence: 96%
“…Although the two aforementioned drugs have been reported to be associated with the treatment of ICH, the mechanisms underlying their therapeutic actions still require further research. In addition, we found that hecogenin has an anti-inflammatory effect that may contribute to the treatment of ICH (Ingawale, Mandlik & Patel, 2019; Ingawale & Patel, 2016; Ingawale & Patel, 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Although the two aforementioned drugs have been reported to be associated with the treatment of ICH, the mechanisms underlying their therapeutic actions still require further research. In addition, we found that hecogenin has an antiinflammatory effect that may contribute to the treatment of ICH (Ingawale et al 2019;Ingawale & Patel 2016;Ingawale & Patel 2018).…”
Section: Discussionmentioning
confidence: 99%